Utilização de resíduo seco de cervejaria na alimentação de frangos de corte - Parpinelli, Wiliam (2016)
The high prices of the raw materials used in diets for the creation of monogastric animals, is forced to search for new food sources mainly as byproducts. Among the various co-products arising from agro-industrial activities, we can mention the potential to brewery waste to partially replace conventional food rations. Given the above, two experiments were conducted at the Teaching Unit and Campus Poultry Research Dois Vizinhos - UTFPR. In the first experiment, which had duration of 1-21 days 714 chicks were used, with average weight 44,7+/- 0,3g, distributed in a completely randomized design with 6 increasing levels of brewery waste inclusion with 7 replicates of 17 animals each. While in the second experiment, with from 21 to 42 days, were used 546 broiler chicks at 21 days old, average weight of 865 +/- 8g, distributed in a design and treatments similar to the first experiment and 14 birds per repetition. The birds were weighed on arrival, 21 and 42 days in experiment I and at 21 and 42 days in the second experiment to determine the performance of animals in these phases. In the first experiment, 21 days, blood samples of two birds were collected by experimental unit and killed 2 birds to assess body composition and development of the intestinal villi and 2 birds at 42 days to assess the possible residual effects of treatments on carcass yield and prime cuts. While in the second experiment, after 42 days of life also blood samples of two birds were collected and slaughtered one bird per experimental unit for assessment of body composition and another one bird by repetition to evaluate the carcass yield and prime cuts and development of the intestinal villi. All birds were sacrificed by cervical dislocation. Statistical analyzes of the studied levels were carried out by the Statistical Analysis System program - SAEG (Universidade Federal de Viçosa - UFV, 1999).